The Role of Legislation in Facilitating the Investment Environment (Iraq a model) - صالح عمر حماد; اللهيبي علي احمد (Journal of Legal Sciences, 2021)
The legislation contributes to facilitating the process of attracting investments to the state, in addition to the importance of strengthening the investment environment, which contributes to encouraging business in all economic fields and establishing the country’s position on the map of preferred destinations for investment at the regional and global levels. With the vision of the state and its strategy to move towards the promising sectors of the economy, leading to comprehensive growth in all sectors at the level of the state economy, and the importance of integration and cooperation between all institutions and government and private departments. The investment-driven factors, supporting the business environment in terms of flexibility of investment legislation, facilitating business establishment and an enabling regulatory environment, and the solid infrastructure that makes it a gateway for investors to global regional markets. It also has the financial capacity to continue to pump money into development projects. The package of government and investment legislation will also consolidate the state’s position on the map of the world’s preferred destinations for investment; the country is a prominent attraction for foreign directly investment, especially as laws and regulations governing investment are starting to open the door for global investors, to own their projects in specific sectors under conditions set by law.